2018
DOI: 10.1182/blood-2018-99-112750
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous Extramedullary Relapse in Multiple Myeloma - A Multicenter Retrospective Study in 127 Patients

Abstract: Background: Hematogenous extramedullary multiple myeloma (HEMM), though rare, is mainly observed in MM patients at relapse. The current study assesses the characteristics and outcomes of patients with MM who develop HEMM in the novel agent era. Methods: Consecutive patients, treated in 16 participating centers and diagnosed with HEMM, were included. Patient characteristics at diagnosis and at HEMM presentation, treatment regimens, response to therapy, response duration and survival were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In a retrospective study of 127 consecutive patients with hematogenous EM relapse [37], first treatments for EMD included PIs (50%), IMiDs (39%), monoclonal antibodies (10%), and chemotherapy (53%). ORR (≥ partial response) was 57% across all treatments and IMiDs were associated with higher ORR compared with PIs (HR 2.2, 95% CI 1.02-4.7; p = 0.04).…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…In a retrospective study of 127 consecutive patients with hematogenous EM relapse [37], first treatments for EMD included PIs (50%), IMiDs (39%), monoclonal antibodies (10%), and chemotherapy (53%). ORR (≥ partial response) was 57% across all treatments and IMiDs were associated with higher ORR compared with PIs (HR 2.2, 95% CI 1.02-4.7; p = 0.04).…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…33 A multicentre study of 127 patients with EMD disease also showed dismal outcome. 78 The prognosis is particularly poor in patients with CNS involvement who have a median survival of <3 months, 38,39 and even when novel agents are used outcomes to date have been dismal. 41,79,80 Survival may be improved by the combination of radiation therapy (cranial or craniospinal) along with systemic plus intrathecal therapy, but this constitutes an area of exquisite unmet medical need.…”
Section: Prognosismentioning
confidence: 99%
“…A few studies have reported association of high-risk cytogenetics like t(4;14), t(14;16), gain (1q21), and del(17p) in patients with EMD [2,24,25]. Studies have also identified del(17p13) and del(13q14) as markers for progression to EMD [2,26] and del(13) as risk factor for EM relapse. Gain (1q) was associated with inferior outcome [27].…”
Section: Cytogenetic Profilementioning
confidence: 99%